Improving the Accuracy and Efficiency of Students’ Attendance Management with a Barcode-Based Digital Attendance System - Resya Fakhrunnisa; Ana Ratnasari; Meita Lesmiaty Khasyar (Jurnal Ilmiah Mandala Education (JIME), 2026)
This study aims to develop and evaluate a barcode-based digital attendance system to improve the efficiency and accuracy of student attendance management at Muhammadiyah University of Bogor Raya. This system is expected to address the problems encountered in the manual attendance process, which relies on one-by-one clicks in SIAKAD. The research method used was an experimental design with a quantitative approach, with data collection through questionnaires, interviews, and direct observation. The main findings of the study indicate that the barcode-based attendance system speeds up the attendance process, from 10-15 minutes using SIAKAD to just 2-3 minutes. Furthermore, 60% of lecturers reported improved attendance recording accuracy, and 80% of administrators felt the system reduced data processing time. This study also showed that the barcode-based system reduces reliance on paper, making it more environmentally friendly. Overall, these findings indicate that the barcode-based attendance system makes a significant contribution to improving administrative efficiency at the university. This research is expected to serve as a reference for the development of attendance systems at other universities with similar goals.